Monthly Mean Sea Ice Data from the Polar Ice Prediction System, the Regional Polar Ice Prediction System - Barents Sea and the Regional Polar Ice Prediction System - Greenland Sea - Posey, P. G.; Preller, R. H. (1994)
The Polar Ice Prediction System (PIPS), the Regional Polar Ice Prediction System - Barents (RPIPS-B) and the Regional Polar Ice Prediction System - Greenland Sea (RPIPS-G) are all operational sea ice forecasting systems that have been run daily at the Fleet Numerical Meteorology and Oceanography Center (FNMOC) since September 1987, June 1989, and October 1991, respectively. The basis for all three models is the Hibler ice model (Hibler, W. D. (1 979). A Dynamic Thermodynamic Sea Ice Model. Journal of Physical Oceanography 9:815-846; Hibler, W. D. (1 980). Modeling a Variable Thickness Sea Ice Cover. Monthly Weather Review 108:1944-1973). The ice models are driven by monthly mean ocean currents and deep ocean heat fluxes derived from the Hibler and Bryan (A diagnostic Ice-Ocean Model. Journal Physical Oceanography 17:987-1015 (1987) coupled ice-ocean model. They are also driven by atmospheric forcing from the Navy Operational Global Atmospheric Prediction System (NOGAPS) (Rosmond, T. E. (1981). NOGAPS: Navy Operational Global Atmospheric Prediction System. In Fifth Conference on Numerical Weather Prediction (Monterey, California), American Meteorological Society, Boston, Massachusetts, preprint volume, 74-79; Hogan et al. (1990). The Description of the Navy Operational Global Atmospheric Prediction System's Forecast Model. Naval Research Laboratory, Monterey, California, NOARL Report 13). Each day a 24-h forecast of PIPS, RPIPS-B, and RPIPS-G is submitted and archived by the Naval Research Laboratory. Sea ice forecasting, Sea ice models, Sea ice analysis.